THE MESSAGE OF EDUCATIONAL CHARACTER WISDOM IN THE MINANGKABAU CLASSIC STORY - Abdurahman Abdurahman (International Conference on Languages and Arts, 2014)
The objective of this paper is to describe the phenomenon of cultural educational wisdom messages in the Minangkabau classic story, especially kaba stories contained in "Cindua Mato". It describes the existence of kaba as a literary work which contains educational wisdom among them: the message about character wisdom of the importance of education; knowledge about learning strategies, learning ethics; and character of educating children in a variety of occasions. This brief discussion is expected to be input to understand and analyze the existence of educational character wisdom in the Minangkabau classic story in the learning literature in the future. Key word: Education wisdom, Classical story of Minangkabau